AKTVITAS DAKWAH JEMAAT AHMADIYAH DAN RESPON MASYARAKAT DI KOTA MANADO - Taufik Bilfaqih; Muhammad Iqbal Suma (Aqlam: Journal of Islam and Plurality, 2019)
Abstract: A century after his presence in 1889 in India, only then did Ahmadiyya expand to Indonesia. Post Joint Decree (SKB) of 3 ministers, namely Minister of Religion, Attorney General and Minister of Home Affairs Number 3 of 2008, Number Kep 33 / A / JA / 6/2008, Number 199 of 2008 concerning Warnings and Orders to Adherents, Members and / or Management Members of the Indonesian Ahmadiyya Community (JAI) and community members, in almost every area the Ahmadiyya Jama'at gets resistance from other Islamic groups. However, it was very different from their existence in the city of Manado, almost no friction and repressive actions were found from adherents of Islamic teachings mainstream. This study wanted to reveal the existence of the Ahmadiyya Jama'at in Manado, starting from the history of arrivals, developments and dynamics of the propaganda of this community. Da'wah in this case the author understands as an activity in carrying out religious rituals as well as a mission in teaching and spreading religious ideas. This research is a field research (field research), because the data and study materials used are from the Ahmadiyya Jama'at in the city of Manado and its surroundings. To support this research, the authors also took data from the library (library research).Keyword: Ahmadiyah, Religious, Dakwah Activity, Society.  Abstrak: Satu abad setelah kehadirannya pada 1889 di India, barulah Ahmadiyah berkembang luas hingga ke Indonesia. Pasca Surat Keputusan Bersama (SKB) 3 menteri, yaitu Menteri Agama, Jaksa Agung dan Menteri Dalam Negeri Nomor 3 Tahun 2008, Nomor Kep 33/A/JA/6/2008, Nomor 199 Tahun 2008 tentang Peringatan dan Perintah kepada Penganut, Anggota dan/atau Anggota Pengurus Jemaat Ahmadiyah Indonesia (JAI) dan warga masyarakat, hampir disetiap daerah Jemaat Ahmadiyah mendapat resistensi dari kelompok Islam lainnya. Namun, berbeda sekali dengan eksistensi mereka di Kota Manado, hampir tidak ditemukan adanya gesekan dan tindakan represif dari penganut ajaran Islam maenstream. Penelitian ini ingin mengungkap keberadaan Jemaat Ahmadiyah di Manado, mulai dari sejarah kedatangan, perkembangan serta dinamika dakwah komunitas ini. Dakwah dalam hal ini penulis pahami sebagai kegiatan dalam menjalankan ritual keagamaan sekaligus misi dalam mengajarkan dan menyebarkan paham keagamaan. Penelitian ini merupakan penelitian lapangan (fieldresearch), karena data dan bahan kajian yang dipergunakan berasal dari Jemaat Ahmadiyah di Kota Manado dan sekitarnya. Untuk menunjang penelitian ini, penulis pun mengambil data dari kepustakaan (library research).Kata Kunci: Jemaat Ahmadiyah; Aliran Kegamaan; Aktivitas Dakwah; masyarakat.